(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2021)
This study aimed to identify the provision and the levels of research skills in the 10th grade Biology Textbook. The sample is a biology textbook named Biologi untuk Kelas X SMA/MA. The units analyzed are only focus on 4 components books, namely Diskusi; Kuis Bio; Tugas Mandiri; and Aktivitas. Research skills referred to the Research Skills Development (RSD) framework developed by Willison and O’Regan. The result of the analysis stated that about 66.21 % of component books identified providing students to have research skills. As for the level of Research Skills, most of it is in level 1 (Prescribed Research).